2019
DOI: 10.1136/bmjopen-2018-024444
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions for the implementation of thromboprophylaxis in hospitalised patients at risk of venous thromboembolism: an updated abridged Cochrane systematic review and meta-analysis of randomised controlled trials

Abstract: ObjectiveTo assess the effectiveness of system-wide interventions designed to increase the implementation of thromboprophylaxis and decrease the incidence of venous thromboembolism (VTE) in hospitalised medical and surgical patients at risk of VTE.DesignSystematic review and meta-analysis of randomised controlled trials (RCTs).Data sourcesMedline, PubMed, Embase, BIOSIS, CINAHL, Web of Science, CENTRAL, DARE, EED, LILACS and clinicaltrials.gov without language restrictions from inception to 7 January 2017, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
0
28
0
2
Order By: Relevance
“…Thrombosis is a major cause of morbidity and mortality worldwide and significantly funds the economic disease burden. [ 9 ] Thrombophylaxis in hospitalized patients markedly decreased the incidence of VTE in that group of patients but, however, lack of public awareness and knowledge of use of thrombophylaxis in at-risk, no hospitalized patients, still contribute to high morbidity and mortality[ 10 ] with multiple calls to enhance public awareness of VTE. [ 11 ] This study provides an overview of awareness and knowledge toward VTE in Aseer region, KSA.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis is a major cause of morbidity and mortality worldwide and significantly funds the economic disease burden. [ 9 ] Thrombophylaxis in hospitalized patients markedly decreased the incidence of VTE in that group of patients but, however, lack of public awareness and knowledge of use of thrombophylaxis in at-risk, no hospitalized patients, still contribute to high morbidity and mortality[ 10 ] with multiple calls to enhance public awareness of VTE. [ 11 ] This study provides an overview of awareness and knowledge toward VTE in Aseer region, KSA.…”
Section: Discussionmentioning
confidence: 99%
“…3 4 Consequently, there has been a substantial and sustained focus on VTE prevention over the last three decades, with good evidence indicating a reduction in morbidity with primary thromboprophylaxis in hospitalised patients. [5][6][7][8] Despite this evidence, thromboprophylaxis remains either underused or inappropriately applied. 9 Risk assessment models (RAMs) have been developed to help stratify the risk of VTE among hospitalised patients.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that most of the interventions followed in these studies were effective at increasing the appropriate prophylaxis, however, the effectiveness level was different between studies (11). Moreover, it was revealed in the updated systematic review, including RCT studies, that alerts interventions involving computer and human alerts are more effective than multifaceted interventions in increasing the appropriate prophylaxis prescriptions and decreasing the incidence of VTE in at risk hospitalized medical and surgical patients (12). Furthermore, studies derived from behaviour change theory to inform the intervention to increase the uptake of VTE guidelines in medical patients were not identi ed in our systematic review study (13).…”
Section: Introductionmentioning
confidence: 99%